Homo ludens w przestrzeni współczesnego miasta - Szalbot, Magdalena (Studia Etnologiczne i Antropologiczne, 2010)
Socio cultural problems of the contemporary city can be considered from the perspective of unusually diversified, yet concrete phenomena, and aspects co creating the city reality. The aim of the paper is to analyse the current state and changes of the contemporary cities, taking into consideration changing ludic needs of the inhabitants. It goes about illustrating how the present day party like behaviours of the city society reflect in the changes of the city space and in which direction they seem to go. On the one hand, the aim of the work is to show how the inhabitants of the contemporary cities, paying more and more attention to attractive forms of spending leisure time, impact on the city, changing it, and on the other hand, how the city alone and the urban life style, giving new stimuli and possibilities in this area, condition the behaviours of the inhabitants. The observations and studies conducted, the results of which were presented in the article, make us aware that the city is, on an unusual scale, becoming a ludic space for a contemporary human being. Socio cultural changes of contemporary cities and urban life style were shown from the perspective of the current state of a ludic sphere of culture on the basis of the examples coming from the city centres of different size, cultural affiliation and situated in different geographical latitude. The main part of the article, on the basis of the cities of a different scale and geographical location, presents some general and contemporary tendencies within the scope of “ludicity” of the spaces of contemporary cities and urban style as a result of unrestrained, grass roots and individual ini¬tiatives of the inhabitants, as well as purposeful and planned urban enterprises the observation and examination of which allows for joining a discussion on widely understood socio cultural problems of the contemporary city.